(untitled) (Pain medicine, 2016)
Acute pain hurts and most often is the result of tissue injury. Chronic pain also hurts. Although those who suffer from chronic pain also tend to associate the onset with an injury, illness, or surgical procedure; the root cause is far more complex. Chronic pain most often does not follow dermatomal distributions associated with any injury, disease or surgical procedure. And more often than not, chronic pain sufferers also suffer from various forms of depression and/or anxiety. The process of central sensitization resulting from tissue injury has been elucidated, as has many of the molecular changes within the brain that perpetuate chronic pain. Genetics, epigenetics, environmental stressors, and emotional stressors all play roles to varying degrees in the development of the chronic pain state. This article explores how synaptic memories form in the brain as a result of both physical and emotional traumas (multiple hits) resulting in progression to chronic pain, because of failure of the brain’s descending modulatory mechanisms to prevent or control “the pain”.